2023
DOI: 10.1039/d2cp04753e
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption properties of small gas molecules on SnSe2 monolayer supported with transition metal: first-principles calculations

Abstract: The adsorption properties of CH4, H2S, SO2, CO, H2O and NO molecules on transition metal-supported SnSe2 surface are investigated by the first-principles method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…[45] And it is close to H 4,4,4 -graphyne (−1.601 eV) [32] as well as Fesupported SnSe 2 (−1.507 eV). [46] A higher E ad value represents higher sensitivity and faster response time. However, it is worth noting that too small or too large values of E ad are not favorable for gas adsorption and desorption, while the range from −2 eV and −1 eV is the most favorable.…”
Section: Effect Of Single Fe Atom Dopingmentioning
confidence: 99%
“…[45] And it is close to H 4,4,4 -graphyne (−1.601 eV) [32] as well as Fesupported SnSe 2 (−1.507 eV). [46] A higher E ad value represents higher sensitivity and faster response time. However, it is worth noting that too small or too large values of E ad are not favorable for gas adsorption and desorption, while the range from −2 eV and −1 eV is the most favorable.…”
Section: Effect Of Single Fe Atom Dopingmentioning
confidence: 99%
“…9,10 Since the discovery of graphene in 2004, 11 two-dimensional (2D) materials have attracted great interest from scientists owing to their excellent physical and chemical properties, such as the large surface-to-volume ratio, excellent carrier mobility, and high stability. 12,13 2D materials such as graphene, [14][15][16] transition metal dichalcogenides, 17,18 transition metal oxides, 19,20 and group-VA materials [21][22][23][24][25][26] have been extensively studied in the application of gas sensors. 27 The lack of band gap restricts the application of graphene in gas sensors even though it exhibits excellent gas-sensitive properties.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the structural and electronic properties of 2D materials may lead to different adsorption strengths, sensitivity, and selectivity of the resulting nano gas sensors. Choosing specific materials to detect and control target gas molecules can significantly improve the efficiency of the sensors. Previous works have shown that graphene can detect toxic gases, such as CO, NO, NO 2 , and NH 3 molecules. , However, phosphorene has a more significant band gap and electron mobility compared with graphene, which results in a higher affinity for gas molecules. , Its calculated gas adsorption energy and sensor sensitivity are significantly higher than graphene. Further studies have indicated that the gas selectivities of 2D materials may diversify greatly. Among graphene, silicene, phosphorene, and MoS 2 , MoS 2 has the highest adsorption intensity for CO molecule, , phosphorene has the most considerable adsorption energy of 0.86 eV for NO molecule, and silicene is the best for detecting NH 3 and NO 2 molecules …”
Section: Introductionmentioning
confidence: 99%